ESCollab: uma metodologia colaborativa voltada para o ensino de Engenharia de Software - Paiva, Severino do Ramo de (2012)
Among all the activities performed by human beings today, software development is one of the most recent in historical terms, but one of the most important due to the increasing digitalization of the society. On the other hand, the growing importance of collaborative environments, in a globalized world, has enabled the sharing of information and the interaction between people far away. These changes have enhanced the power of teamwork and social interaction. The social and economic importance of the software industry has motivated many researchers to seek solutions to improve the training of skilled labor in the area of Software Engineering. This dissertation work presents a collaborative teaching methodology aimed at improving the teaching of the disciplines of Software Engineering. The ESCollab methodology incorporates the latest teaching tools and has been applied, as a case study, in two institutions of higher education in computing.